Sosialisasi Literasi Digital Sehat: Upaya Mengurangi Risiko Bahaya Gadget bagi Anak SD di Desa Kediri Selatan, Lombok Barat - raehanah (Postgraduate Program, University of Mataram, 2026)
The development of digital technology has created both opportunities and challenges for elementary school–aged children. Gadgets can serve as interactive learning media, sources of information, and tools for fostering creativity; however, uncontrolled use can lead to various negative impacts, including exposure to harmful content, reduced social interaction, and physical as well as mental health problems. This community service program aims to instill awareness of healthy digital literacy among elementary school students in South Kediri, West Lombok, as a preventive effort against the potential dangers of gadget use. The method employed is Participatory Action Research (PAR), involving teachers and students in stages of problem identification, planning, action implementation, observation, and evaluation. The outreach was conducted in four elementary schools (SDN 1, SDN 2, SDN 3, and SDN 4 Kediri Selatan) targeting fifth- and sixth-grade students through interactive lectures and educational games. The results show that students were highly enthusiastic and actively participated throughout the activities. Evaluation through pre-test and post-test revealed a significant improvement in students’ understanding—for instance, in managing gadget usage time (from 16% to 70%), recognizing harmful digital content (from 30% to 76%), and understanding media ethics (from 25% to 76%). These findings confirm that promoting healthy digital literacy effectively enhances students’ critical awareness and positive attitudes toward gadget use. Consequently, this program contributes to preventing the negative effects of gadgets while supporting the strengthening of character education in the digital era